The role of beliefs about aggression in cyberbullying and animal abuse - Sanders, Cheryl E. (Psychology, crime & law, 2018)
The current study sought to examine the associations between involvement in bullying (traditional and cyber), attitudes about aggression, and animal abuse. Four hundred and thirty-nine undergraduate students (267 females and 172 males) enrolled in Introductory Psychology completed surveys assessing bullying involvement, normative beliefs about aggression, and animal abuse tendencies. Results revealed that animal abusers reported significantly higher rates of bullying (traditional and cyber) and significantly more accepting views of aggression when compared to non-abusers. A logistic regression model indicated that bullying perpetration (traditional and cyber), normative beliefs about aggression, and gender were significant predictors of animal abuse. In addition, the findings suggest that normative beliefs about aggression may serve as an underlying mechanism linking traditional bullying, cyberbullying, and animal abuse. Implications for prevention and intervention programs for aggression toward humans and animals are discussed.